Bokus Barbara – Kosowska Ewa (eds.), Truth and Falsehood in Science and the Arts (Warszawa: Wydawnictwa Uniwersytetu Warszawskiego 2020) - Rabiej, Stanisław Jan (Verbum Vitae, 2021)
Review of the book: Bokus Barbara – Kosowska Ewa (eds.), Truth and Falsehood in Science and the Arts (Warszawa: Wydawnictwa Uniwersytetu Warszawskiego 2020). Pp. 299. ISBN 978-83-235-4220-9